2016
DOI: 10.1038/srep39386
|View full text |Cite
|
Sign up to set email alerts
|

Bmi1-positive cells in the lingual epithelium could serve as cancer stem cells in tongue cancer

Abstract: We recently reported that the polycomb complex protein Bmi1 is a marker for lingual epithelial stem cells (LESCs), which are involved in the long-term maintenance of lingual epithelial tissue in the physiological state. However, the precise role of LESCs in generating tongue tumors and Bmi1-positive cell lineage dynamics in tongue cancers are unclear. Here, using a mouse model of chemically (4-nitroquinoline-1-oxide: 4-NQO) induced tongue cancer and the multicolor lineage tracing method, we found that each uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…This chemical is used to generate an oral cancer model in mice and rats. 4-NQO is administered either locally on the tongue or adding 4NQO to the drinking water [165,166,167]. Long-term administration of 4-NQO leads to a progression of carcinogenesis and includes hyperplasia, dysplasia, preneoplastic as well as neoplastic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…This chemical is used to generate an oral cancer model in mice and rats. 4-NQO is administered either locally on the tongue or adding 4NQO to the drinking water [165,166,167]. Long-term administration of 4-NQO leads to a progression of carcinogenesis and includes hyperplasia, dysplasia, preneoplastic as well as neoplastic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Further, specific targeting and pharmacological inhibition of BMI-1 can inhibit tumor sphere formation and reduced tumorigenesis in TSCC [ 47 , [112] , [113] , [114] ]. Toshihiro Tanaka and co-workers (2016) used multicolor lineage tracing method and revealed that BMI1-positive tumorigenic cells display TCSC-like characteristics in a chemically induced tongue cancer mouse model [115] . Further, inhibition of BMI-1 through PTC-209, PTC596 inhibitors reduced BMI-1 expression, tumorsphere formation, the percentage of ALDH1 +ve subpopulation and increased chemosensitivity against 5-FU and cisplatin in TSCC cells ( Table 2 ) [ 51 , 112 , 114 , 116 ].…”
Section: Various Molecular Approaches/signaling Pathways For Targetinmentioning
confidence: 99%
“…Altered expression of BMI-1 has been found to be correlated with self-renewal of CSC in HNC [ 47 , 140 ]. BMI-1 +ve CSCs in TSCC cells have been associated with drug resistance in a mouse model [ 115 , 141 ]. Recently, Chen and co-workers (2017) investigated that BMI-1 +ve CSCs can mediate invasive growth and lymph node metastasis in a mouse model and the primary oral tumors associated with high tumorigenicity, invasiveness and cisplatin-resistance leading to overexpression of transcription factor activator protein-1 (AP-1) [142] .…”
Section: Various Molecular Approaches/signaling Pathways For Targetinmentioning
confidence: 99%
“…Consistently, BMI1 overexpression is highly correlated with malignant phenotypes and thereby causes malignant transformation in HCC [ 219 , 220 , 221 ]. Aberrant BMI1 expression contributes to the maintenance of CSC subpopulations in multiple types of cancer [ 34 , 222 , 223 , 224 ]. Additionally, BMI1 is involved in the maintenance of the tumorigenic SP subpopulation in liver cancer [ 113 ].…”
Section: Signaling Pathway-based Therapiesmentioning
confidence: 99%